Strategic Change Management Model in The Islamic Life Insurance Industry - Fitri Hartati; Irfan Syauqi Beik; Ujang Sumarwan; Popong Nurhayati (Greenation International Journal of Economics and Accounting, 2026)
The Islamic life insurance industry in Indonesia has experienced significant growth; however, its market share remains relatively low compared to conventional insurance, indicating the presence of structural gaps and strategic challenges. This study aims to develop a strategic change management model that enhances competitiveness and supports sustainable business transformation in the Islamic life insurance industry. The research employs a mixed qualitative approach by integrating Soft System Methodology (SSM), Analytical Hierarchy Process (AHP), and Interpretative Structural Modeling (ISM) to analyze complex problems, identify key factors, and design a comprehensive change model. The findings reveal that the industry faces multidimensional challenges, including low financial literacy, limited human resource competencies, weak product differentiation, and insufficient digital transformation. Furthermore, external pressures such as regulatory dynamics and increasing competition intensify the need for strategic adaptation. The proposed model emphasizes the integration of internal capabilities and external market dynamics, supported by innovation, digital transformation, and stakeholder collaboration. The study contributes to the literature by offering a holistic and structured framework for managing strategic change in the Islamic life insurance sector. Practically, the model provides guidance for industry players and regulators to improve performance, expand market share, and strengthen the sustainability of Islamic financial institutions in a dynamic business environment.